METHODOLOGICAL APPROACHES TO STRATEGIC PLANNING OF UNITED LOCAL COMMUNITIES DEVELOPMENT - Vasylchenko , G. V.; Vasylchenko S. М.; Verbovska , L. S. (The actual problems of regional economy development, 2017)
Important aspects of strategic planning of development of united local communities: possibilities of local self-government, priorities of development, approaches and methods of development of the Strategy are considered in the article. The authors use practical experience of “Business initiatives Public centre” (Ivano-Frankivsk) in working out the Strategies of local economic development for Bilshivtsi, Halych and Burshtyn potential united local communities, and also for Starobohorodchany united local community of Ivano-Frankivsk region. Materials of the article can be useful for scientists, activists and leaders of local communities, who created, or prepare themselves for creation of their united local communities.